Translation to German and linguistic validation of the Rapid Assessment of Physical Activity (RAPA) questionnaire - Stefan Tino Kulnik; Johanna Gutenberg; Kathrin Mühlhauser; Tari Topolski; Rik Crutzen (SpringerOpen, 2023)
Abstract Purpose To produce a culturally adapted translation of the Rapid Assessment of Physical Activity (RAPA) questionnaire for German speaking Austrians and to conduct a linguistic validation of the new language version. Methods The original English RAPA questionnaire was translated into German for Austria and underwent an independent forward and back translation, followed by cognitive debriefing interviews with older adults aged 55 to 78 years with and without health conditions (n = 13), for linguistic validation. Results Several distinct choices were made in the translation of the RAPA questionnaire to German, including the use of colloquial terms for 'physical activity' and 'intensity'; and the decision to keep to the original examples and images of different physical activities for illustrating the intensity levels (light, moderate, vigorous) of physical activity. In cognitive debriefing, interviewees commented that some example activities for the respective intensity levels could - depending on the individual - also represent a higher or lower intensity level; and that the wording of RAPA items 4 and 5, which describe the category 'under-active regular' aerobic activity, was difficult to understand. Both issues were addressed and resolved through minor iterative modifications made during the cognitive debriefing process. Conclusions A new version of the RAPA questionnaire in German for Austria has been produced by forward and back translation and linguistic validation. The questionnaire may now undergo psychometric evaluation.